Sensitive data donation in practice: unforeseen challenges and lessons learned - Gómez Ortega, Alejandra (Frontiers in Human Dynamics, 2025)
Data donation is increasingly being used to collect personal data for scientific research. Through it, researchers directly interact with individuals and communities as they invite them to contribute to a specific research project by donating their data. This practice is facilitated by the ubiquity of products and services collecting data in people's daily lives, which means data is already available and could potentially be re-used. Additionally, it is enabled by recent directives such as the General Data Protection Regulation in Europe, which gives individuals the right to access their data. From 2020 to 2024, I investigated and applied data donation following a Research through Design process across three case studies, each focusing on different data. In this paper, I briefly introduce the case studies, reflect on my experience, and discuss the unforeseen challenges I faced and the practical considerations I learned from these. I hope these can aid researchers and practitioners in applying and further developing data donation research.